Fake news and covid-19: a concern due to the low vaccine coverage in Brazil - Dennis Minoru Fujita; Luiz Henrique da Silva Nali; Giselle Pacífico Sartori; Andrés Jimenez Galisteo; Heitor Franco de Andrade Jr; Expedito José de Albuquerque Luna (Universidade de São Paulo, 2022)
Abstract This study comprised the application of a survey in São Paulo, Brazil, in 2 different periods of 2020: the beginning of the covid-19 pandemic and the disease's first peak (from March to April, 100 interviews) to the time of stability in case fatality rates (from May to July, 100 interviews); the questionnaire included was composed of 14 multiple-choice questions to evaluate the importance of mass communication channels, including social media, and the level of importance attributed to preventive measures at the beginning of the pandemic. The changes in people's behavior, even in a group with more schooling, which initially considered preventive measures to be very important (91%) but, in the second survey, was reduced to 82%. The reinforcement of preventive measures to reduce cases and deaths by covid-19 in Brazil is urgent, allied to recommendations with clear information on the importance of vaccination to avoid low rates as the current situation of vaccine coverage for preventable diseases.